Teacher's Approach in Increasing the Interpersonal Intelligence of Children aged 5-6 years in Cingkang Village - Nuraisyah Nuraisyah; Umaemah Marsuki AR; Andi Hidayah Insani; Herman Herman; Rusmayadi Rusmayadi (EduLine: Journal of Education and Learning Innovation, 2024)
The aim of this research is to develop children's interpersonal intelligence. One of the strategies that can be used by teachers is participatory cooperative learning strategies. The method used in this research is a descriptive method with a qualitative approach. The data collection technique was carried out using triangulation (combination), data analysis was inductive. And the data taken in this research comes from observations, interviews and documentation. Research findings in the field show that children in group B who make mistakes will more easily admit their mistakes if they are given advice and guidance, so that the children are able to take responsibility for the mistakes they have made.